KAJIAN LITERATUR TENTANG IMPLEMENTASI MODEL ICARE DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KREATIF - Sumingar, Nadia Lintang; Munawaroh, Fa'ijatul; Jariyah, Ita Ainun (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
21st-century education requires students to master 21st-century skills and higher-order thinking skills in line with the Merdeka Curriculum for developing the Profil Pelajar Pancasila, namely critical and creative thinking skills. Based on the results of the PISA Survey, critical and creative thinking skills in Indonesia are still low, as teachers continue to face obstacles in implementing relevant learning models to develop these skills. This study aims to analyze the implementation of the ICARE model in enhancing critical and creative thinking skills. The study employs a Systematic Literature Review (SLR) method, with data collected from 8 international articles and 10 national articles published in the last five years (2021–2025) through Google Scholar and ScienceDirect using the keywords “ICARE Model, Critical Thinking Skill, and Creative Thinking Skill.” The results indicate that the implementation of the ICARE model can improve critical and creative thinking skills, as its stages Introduction, Connection, Application, Reflection, and Extension facilitate students in developing analysis, evaluation, and inference in the indicators of critical thinking, as well as fluency, flexibility, originality, and elaboration in the indicators of creative thinking. Therefore, it can be concluded that the ICARE model is a relevant learning model to foster critical and creative thinking skills through an interactive, contextual, and student-centered approach.